Behaviour, developmental problems and factors associated with excessive screen time in children less than 18 months old - Musa, Husna (2025)
Introduction: In today’s world, the use of screen devices among young children is rapidly increasing, despite no access to screen time being recommended for children below the age of two. Numerous studies have highlighted the undesirable effects of excessive screen time on the developmental, psychosocial, and physical health of children. Objective: The aim of this study is to determine the risk for behaviour and developmental problems and factors associated with excessive usage of screen time in children at 18 months of age. Methods: A cross-sectional study was conducted among the parents of children aged 18 months in four primary health clinics in the district of Sepang. Parents responded to questionnaire including a Developmental Checklist and Baby Paediatric Symptom Checklist (BPSC) was used to screen risk for behaviour problems. Screen time more than 1 hour is defined as excessive. Results: A total of 254 study participants with mean age of 18 months, 134 children (52.8%) were male, most participants were the eldest child (39.8%%) and Malay ethnicity (91.3%). More than half (66.1%) had screen time of less than one hour. Children that were cared in a mixed care environment showed 3.10 times more likelihood of excessive screen time. No significant association was found between screen time and developmental risk. We found a higher proportion of participants scored more than three on BPSC in those with more than one-hour screen time, however this was not significant (p=0.475). Conclusion: We found no significant association between screen time and risk for developmental and behaviour problems. However, one third of the study participants were engaged in excessive screen time. Further studies especially interventional are recommended to promote healthy screen time practice in children.